2008
DOI: 10.1073/pnas.0705181105
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of AP-1–NF-κB ternary complexes in living cells by using a BiFC-based FRET

Abstract: Venus ͉ Cerulean ͉ YFP ͉ cross-talk ͉ NFAT P rotein-protein interactions play a pivotal role in mediating signal-transduction pathways and executing cellular functions. Defining how each protein interacts with all possible partners in cells provides insight into cellular roles of individual proteins. This task has become more demanding given that many interacting networks have been generated in the postgenome era (1, 2). Although a number of methods are available for protein interaction study, several fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 50 publications
4
102
0
1
Order By: Relevance
“…Recent experiments using the BiFC-based FRET (BiFC-FRET) assay for visualization of complexes in living cells has shown that NF-κB and AP-1 (jun/fos) interact in the nucleus to form tertiary complexes [9]. In the TNF-stimulated state, we show using re-ChIP analysis that AP-1 factors and NF-κB combine to form a complex not seen in the basal state.…”
Section: Discussionmentioning
confidence: 67%
“…Recent experiments using the BiFC-based FRET (BiFC-FRET) assay for visualization of complexes in living cells has shown that NF-κB and AP-1 (jun/fos) interact in the nucleus to form tertiary complexes [9]. In the TNF-stimulated state, we show using re-ChIP analysis that AP-1 factors and NF-κB combine to form a complex not seen in the basal state.…”
Section: Discussionmentioning
confidence: 67%
“…The possible impaired expression and/or activation of TAK1 and Tpl-2 in Fra-1 Tg mice need to be further explored. The direct association between AP-1 and NF-kB might also be a mechanism (35). One intriguing possibility is that the AP-1 and NF-kB pathways are reciprocally regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The vectors pBiFC-VN173 and pBiFC-VC155 were kindly provided by Dr. Chang-Deng Hu from Purdue University ( 15 ). Fulllength mouse FSP27 cDNA was cloned into the EcoR I/ Xho I site of the pBiFC-VC155.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%